2010
DOI: 10.3168/jds.2010-3356
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between endometritis and metabolic state during the transition period in pasture-grazed dairy cows

Abstract: The primary objective of this study was to identify relationships between endometritis and metabolic state during the calving transition and early lactation periods. A subset of mixed age and breed dairy cows (n=78) from a seasonal, pasture-grazed herd of 389 cows was examined. The selected cows were grouped as having endometritis at d 42 postpartum or being unaffected by endometritis. Endometritis was defined as >6% (upper quartile) of uterine nucleated cells being polymorphonuclear cells (H-PMN; n=38); unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
88
5
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 39 publications
19
88
5
5
Order By: Relevance
“…In another investigation the concentrations of serum Hp and SAA were significantly higher in cows with acute puerperal metritis than in clinically healthy animals and furthermore among successfully pregnant cows the number of days open was significantly higher in cows with high concentrations of Hp indicating that subclinical uterine infection could be contributing to the prolongation of days open and a poor conception rate. In contrast a study of endometritis which compared the metabolic state of cows between those with high and low levels of elevated intrauterine polymorphonuclear cells [187], did not find a significant difference in serum Hp between groups although elevations were seen in both groups on the day of parturition. However, it was noted that the study design excluded cows with severe metritis.…”
Section: Acute Phase Proteins In Ruminant Reproductionmentioning
confidence: 81%
“…In another investigation the concentrations of serum Hp and SAA were significantly higher in cows with acute puerperal metritis than in clinically healthy animals and furthermore among successfully pregnant cows the number of days open was significantly higher in cows with high concentrations of Hp indicating that subclinical uterine infection could be contributing to the prolongation of days open and a poor conception rate. In contrast a study of endometritis which compared the metabolic state of cows between those with high and low levels of elevated intrauterine polymorphonuclear cells [187], did not find a significant difference in serum Hp between groups although elevations were seen in both groups on the day of parturition. However, it was noted that the study design excluded cows with severe metritis.…”
Section: Acute Phase Proteins In Ruminant Reproductionmentioning
confidence: 81%
“…Williams et al (2005) concluded that uterine infection also affects ovarian function; however, in this work, the presence or absence of CL had no effect on the incidence of subclinical endometritis. In a study conducted by Burke et al (2010), using the endometrial cytobrush technique, noticed that cyclic cows diagnosed with low amounts of PMN cells ovulated early (between 63 and 70 days postpartum) when compared with those with high levels of these cells, which took longer to ovulate. It is important to notice that the presence of CL affects the recovery of the uterus after parturition, directly interfering in the future reproductive performance.…”
Section: Discussionmentioning
confidence: 97%
“…Circulating numbers of leucocytes (including both mature and immature PMN) increase to peak at or just after calving, and these counts were similar between cows with and without a fatty liver (>40 mg fat/g liver in the first 2 weeks postpartum) [9].Other markers of liver health have also been associated with endometritis. In pasture-based cows at weeks 2, 4 and 6, the postpartum aspartate aminotransferase and at weeks 4 and 6, the glutamate dehydrogenase were higher in cows with endometritis at week 6 [10]. Plasma albumin was slightly but significantly lower throughout the transition period in cows that had endometritis.…”
Section: Introductionmentioning
confidence: 84%